The Influence of Scale on School Performance - Robert Bickel; Craig Howley (Arizona State University, 2000)
In this study, we investigate the joint influence of school and district size on school performance among schools with eighth grades (n=367) and schools with eleventh grades in Georgia (n=298). Schools are the unit of analysis in this study because schools are increasingly the unit on which states fix the responsibility to be accountable. The methodology further develops investigations along the line of evidence suggesting that the influence of size is contingent on socioeconomic status (SES). All previous studies have used a single-level regression model (i.e., schools or districts). This study confronts the issue of cross-level interaction of SES and size (i.e., schools and districts) with a single-equation-relative-effects model to interpret the joint influence of school and district size on school performance (i.e., the dependent variable is a school-level variable). It also tests the equity of school-level outcomes jointly by school and district size. Georgia was chosen for study because previous single-level analysis there had revealed no influence of district size on performance (measured at the district level). Findings from this study show substantial cross-level influences of school and district size at the 8th grade, and weaker influences at the 11th grade. The equity effects, however, are strong at both grade levels and show a distinctive pattern of size interactions. Results are interpreted to draw implications for a "structuralist" view of school and district restructuring, with particular concern for schooling to serve impoverished communities. The authors argue the importance of a notion of "scaling" in the system of schooling, advocating the particular need to create smaller districts as well as smaller schools as a route to both school excellence and equity of school outcomes.